21st Century Skills sebagai Upaya Pengembangan Kapabilitas Siswa SMK di Fourth Industrial Revolution Era - Anis Kurniawan; Amat Mukhadis; Widiyanti Widiyanti (Graduate School of Universitas Negeri Malang, 2019)
Abstract: The high number of job seekers and low-level students who dare to become job creators indicates that the capabilities of vocational students in the fourth industrial revolution era are very low. This research aims at finding out the contribution of 21st century skills to the capabilities of vocational students. The research employed with quantitative approach, uses a test of causality relationship with correlation and regression analysis techniques. The results showed that 21st century skills had a causal relationship with students' abilities significantly. The contribution of 23% showed that 21st century skills were an alternative solution in developing student capabilities in the era of the fourth industrial revolution.Abstrak: Tingginya angka pengangguran pencari kerja (job seeker) lulusan SMK dan sedikit siswa yang berani menjadi pencipta lapangan kerja (job creator) mengindikasikan bahwa kapabilitas siswa SMK di era revolusi industri keempat (forth industrial revolution era) sangat rendah. Tujuan penelitian ini untuk mengetahui sumbangan 21st century skills sebagai upaya dalam mengembangkan kapabilitas siswa. Penelitian dilakukan dengan pendekatan kuantitatif menggunakan uji hubungan kausalitas dengan teknik analisis regresi. Hasil penelitian menunjukkan bahwa 21st century skills memiliki hubungan kausal dengan kapabilitas siswa secara signifikan. Besar sumbangan 23% menunjukkan bahwa 21st century skills merupakan solusi alternatif dalam mengembangkan kapabilitas siswa di era revolusi industri keempat.